PENGEMBANGAN BAHAN AJAR DIGITAL BERBASIS WEBSITE CANVA PADA MATERI PEMBELAJARAN PERSATUAN DAN KESATUAN MATA PELAJARAN PANCASILA KELAS III DI MIS NU PALANGKA RAYA - Muhammad Fikri Al-Ghani, Rahmad, Muhammad Syabrina, Rahmadina Alini, (FKIP UMN ALWASHLIYAH, 2025)
This research led to the development of digital teaching materials based on the Canva website to create material on Unity and Integrity for Pancasila Education for third graders at MIS NU Palangka Raya. The product was created using the ADDIE method, starting with needs analysis, design, development, and direct classroom trials. Data were collected through observation, interviews, and several questionnaires from material experts, design experts, class teachers, and students. Validation results showed that the developed teaching materials were considered very suitable for use, with material experts giving a score of 96.6%, design experts 95.9%, class teachers 97.05%, and field trials with students reaching 91.35%. Furthermore, pretest and posttest results showed significant learning improvements, as evidenced by a t-test with a significant value of 0.00 and an average N-Gain of 0.72 (high category). Overall, this digital teaching material has been proven to help students better understand the material, increase their enthusiasm for learning, and make the learning process more engaging and in line with technological developments.